Secretory Products of Trichinella spiralis Muscle Larvae and Immunomodulation: Implication for Autoimmune Diseases, Allergies, and Malignancies - Ljiljana Sofronic-Milosavljevic; Natasa Ilic; Elena Pinelli; Alisa Gruden-Movsesijan (Journal of Immunology Research)
Trichinella spiralis has the unique ability to make itself “at home” by creating and hiding in a new type of cell in the host body that is the nurse cell. From this immunologically privileged place, the parasite orchestrates a long-lasting molecular cross talk with the host through muscle larvae excretory-secretory products (ES L1). Those products can successfully modulate parasite-specific immune responses as well as responses to unrelated antigens (either self or nonself in origin), providing an anti-inflammatory milieu and maintaining homeostasis. It is clear, based on the findings from animal model studies, that T. spiralis and its products induce an immunomodulatory network (which encompasses Th2- and Treg-type responses) that may allow the host to deal with various hyperimmune-associated disorders as well as tumor growth, although the latter still remains unclear. This review focuses on studies of the molecules released by T. spiralis, their interaction with pattern recognition receptors on antigen presenting cells, and subsequently provoked responses. This paper also addresses the immunomodulatory properties of ES L1 molecules and how the induced immunomodulation influences the course of different experimental inflammatory and malignant diseases.